2018
DOI: 10.4314/wsa.v44i4.25
|View full text |Cite
|
Sign up to set email alerts
|

Development of Consumer Perception Index for assessing greywater reuse potential in arid environments

Abstract: Arab countries are primarily situated in arid environments and face serious water scarcity challenges due to growing populations, urbanization, and climate change impacts. Reusing greywater, if adequately treated at the point of generation, poses less human health risk as compared to blackwater reuse. Consumers have several reasons for being unwilling to reuse greywater, including potential health risk, religious and cultural concerns, and feeling uncomfortable. There are several possible reuse applications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…This is also confirmed by other studies: in one study, nearly 80% of respondents would only be willing to invest in grey water systems in the event of significant subsidies or tax breaks [58]. In further studies, concerns about grey water use can be observed for religious and cultural reasons [57]. In contrast, surveys conducted in 12 countries indicate that hygiene concerns were the greatest concern related to the acceptance of grey water, especially in countries with significant water resources [58].…”
Section: Analysis Of Overall Performancesupporting
confidence: 59%
See 1 more Smart Citation
“…This is also confirmed by other studies: in one study, nearly 80% of respondents would only be willing to invest in grey water systems in the event of significant subsidies or tax breaks [58]. In further studies, concerns about grey water use can be observed for religious and cultural reasons [57]. In contrast, surveys conducted in 12 countries indicate that hygiene concerns were the greatest concern related to the acceptance of grey water, especially in countries with significant water resources [58].…”
Section: Analysis Of Overall Performancesupporting
confidence: 59%
“…However, only 25% of the respondents were willing to use grey water for cooking [56]. In contrast, research conducted in Oman indicated that acceptable uses of treated grey water mainly included watering plants, washing floors, landscaping, and flushing toilets [57]. Other studies indicated that people would readily use treated grey water for purposes such as laundry, toilet flushing, car washing, and vegetable irrigation [58,59].…”
Section: Analysis Of Overall Performancementioning
confidence: 99%
“…However, this could be not enough. A recent study conducted by Shafiquzzaman et al [156] focused on consumers' perception of water reuse products shows how it is necessary to develop a Consumer Perception Index (CPI) for assessing reclaimed wastewater reuse potential. The starting point to develop this index is the conception of consumer perception.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to acceptable uses, most found reduction in acceptance as the reused water gets closer to human contact (Oteng-Peprah 2018). Shafiquzzaman et al (2018) propose developing an index of public perceptions for water reuse to determine whether reuse infrastructure projects should even be initiated. These trends reflect the importance of psychological factors and contrast with the view of socio-technological impediments are the greatest challenge to widespread adoption of reuse practices (Larsen et al 2016).…”
Section: Introductionmentioning
confidence: 99%